Nucleoprotein of a Rice Rhabdovirus Serves as the Effector to Attenuate Hemolymph Melanization and Facilitate Viral Persistent Propagation in its Leafhopper Vector - Zhang, Ruonan; Zhang, Xiao-Feng; Chi, Yunhua; Xu, Yuanyuan; Chen, Hongyan; Guo, Zhongxin; Wei, Taiyun (Frontiers in Immunology, 2022)
Melanization in the hemolymph of arthropods is a conserved defense strategy against infection by invading pathogens. Numerous plant viruses are persistently transmitted by insect vectors, and must overcome hemolymph melanization. Here, we determine that the plant rhabdovirus rice stripe mosaic virus (RSMV) has evolved to evade the antiviral melanization response in the hemolymph in leafhopepr vectors. After virions enter vector hemolymph cells, viral nucleoprotein N is initially synthesized and directly interacts with prophenoloxidase (PPO), a core component of the melanization pathway and this process strongly activates the expression of PPO. Furthermore, such interaction could effectively inhibit the proteolytic cleavage of the zymogen PPO to active phenoloxidase (PO), finally suppressing hemolymph melanization. The knockdown of PPO expression or treatment with the PO inhibitor also suppresses hemolymph melanization and causes viral excessive accumulation, finally causing a high insect mortality rate. Consistent with this function, microinjection of N into leafhopper vectors attenuates melanization and promotes viral infection. These findings demonstrate that RSMV N serves as the effector to attenuate hemolymph melanization and facilitate viral persistent propagation in its insect vector. Our findings provide the insights in the understanding of ongoing arms race of insect immunity defense and viral counter-defense.